Kenyan Millennials’ Socialization effect on Customer Dispositions and Customer Enablers on Brand Loyalty (African Multidisciplinary Journal of Research, 2024)
As millennials increasingly turn to online platforms for brand purchases, even for low-involvement products, the pivotal role of social media in strengthening brand loyalty becomes evident. While prior research has explored customer dispositions and enabling factors in relation to brand loyalty, the impact of consumer socialization has been largely overlooked. This study investigates the moderating influence of consumer socialization on the connection between customer dispositions, enabling factors, and brand loyalty. Existing studies have established that customer attitudes and enabling factors shape brand loyalty, but there is limited research focusing on the consumer socialization of local millennials. Grounded in generational theory, the research targeted 399 respondents aged between 23 and 43. Employing a multi-stage sampling process, a self-report questionnaire, utilizing a Likert scale, was employed, and data analysis involved Hierarchical Structural Equation Regression Analysis and Hayes PROCESS. Findings reveal that millennials exhibit loyalty to brands that offer lower associated risks, establish positive emotional connections, and cater to their specific needs. Customer dispositions demonstrated significant relationships with brand trust, brand impact, and brand relevance at a significance level of 0.05. Moreover, customer enablers, customer switching costs, and customer commitment showed statistical significance at the 0.05 level. Consumer socialization was found to moderately connect customer attitudes, enablers, and toothpaste brand loyalty among millennials at the 0.05 significance level. Millennials value brands that demonstrate commitment to customers but have high switching costs. Additionally, millennials maintain limited brand-related relationships due to a limited interest in forming personal connections. Brand managers can formulate strategies aimed at cultivating brand affinity, trustworthiness, and relevance, as millennials place great emphasis on commitment and are deterred by high switching expenses. Future research should comprehensively assess the role of social media in shaping millennials' brand loyalty.